2020
DOI: 10.1021/acs.jpca.0c00877
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine Structure Constants on the Relativistic Coupled Cluster Level with Associated Uncertainties

Abstract: Accurate predictions of hyperfine structure (HFS) constants are important in many areas of chemistry and physics, from the determination of nuclear electric and magnetic moments to benchmarking of new theoretical methods. We present a detailed investigation of the performance of the relativistic coupled cluster method for calculating HFS constants withing the finite-field scheme. The two selected test systems are 133 Cs and 137 BaF. Special attention has been paid to construct a theoretical uncertainty estimat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 96 publications
4
40
2
Order By: Relevance
“…Recently, uncertainties of the hyperfine constants arising in relativistic coupled cluster computations have been studied. 39 It is clear from the above that a proper description of the Yb atom and the YbF molecule requires an accurate treatment of both spin-orbit coupling and electron correlation, for ground as well as excited states. A popular approach is the so-called two-step approach to spin-orbit coupling (SOC), in which electron correlation methods based on non-relativistic or scalar relativistic Hamiltonians are used to obtain excited state energies, that are in turn used to dress a spin-orbit configuration interaction (SOCI) matrix.…”
Section: -11 and References Therein)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, uncertainties of the hyperfine constants arising in relativistic coupled cluster computations have been studied. 39 It is clear from the above that a proper description of the Yb atom and the YbF molecule requires an accurate treatment of both spin-orbit coupling and electron correlation, for ground as well as excited states. A popular approach is the so-called two-step approach to spin-orbit coupling (SOC), in which electron correlation methods based on non-relativistic or scalar relativistic Hamiltonians are used to obtain excited state energies, that are in turn used to dress a spin-orbit configuration interaction (SOCI) matrix.…”
Section: -11 and References Therein)mentioning
confidence: 99%
“…Recently, uncertainties of the hyperfine constants arising in relativistic coupled cluster computations have been studied. 39 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, [14] it was demonstrated that the same computational approach applied for the nearest neighbor of iodine in the periodic table ( 125 Te) leads to complete agreement with the experiment. In support of this choice, it should also be noted that P. Haase et al [15] recently reported that the use of both the two-component X2 C and four-component Dirac-Coulomb Hamiltonians yields practically identical results for other neighbors of 127 I: 137 Ba and 133 Cs.…”
Section: Resultsmentioning
confidence: 81%
“…As already mentioned, the latter allowed for a detailed study of the emblematic U 2 molecule, demonstrating that the spin-orbit interaction reduces the bond order from five 222 to four. 86 The MRCI and CC methods implemented in DIRAC that account for more dynamic correlation have, combined with the experiment, provided reference values for properties such as nuclear quadrupole moments, 223,224 hyperfine structure constants, 225 and Mössbauer isomer shifts. 226 DIRAC also provides theoretical input for spectroscopic tests of fundamental physics, within both the standard model of elementary particles 227 and tests of Beyond Standard Model (BSM) theories that give rise to electric dipole moments of fermions.…”
Section: Discussionmentioning
confidence: 99%